Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat Pasien Diabetes Mellitus Tipe II di Wilayah Kerja Puskesmas Salewangeng - Ikdafila Ikdafila; Nirmawati Darwis; Ruslang Ruslang; Arni AR (Journal Research of Nursing & Midwifery (JRNM), 2025)
Type II Diabetes Mellitus is a chronic disease that requires long-term treatment, including adherence to taking medications, to prevent complications. Therefore, this study aims to determine the relationship between family support and medication adherence of patients with Type II Diabetes Mellitus in the work area of Salewangeng Health Center. This study uses a cross sectional design involving 65 respondents selected by purposive sampling technique. Data were collected through questionnaires to measure Family Support and medication adherence. Analysis performed with The Chi-Square test. The results showed that there was a significant relationship between the relationship of family support with adherence to taking medication (the value of p= 0.000 < 0.05). Overall, this study concluded that there is a significant relationship between family support and adherence to taking medication in patients with Type II diabetes mellitus in the work area of the Salewangeng Health Center.